Seropositive Neuromyelitis Optica (Devics Disease): A Rare Case Report (Journal of Medicine, 2016)
Neuromyelitis optica or Devics disease is a rare inflammatory demyelinating autoimmune disease of the central nervous system which affects the spinal cord and optic nerves and usually associated with increased disability and morbidity. The purpose of this case report is to present this rare disease and focus on diagnostic criteria. NMO is often misdiagnosed as Multiple Sclerosis. The discovery of neuromyelitis optica (NMO) immunoglobulin G (IgG), directed against aquaporin-4 (AQP4), has dramatically changed the clinical definition of NMO and is important in the diagnostic criteria of this disease. Also longitudinally extensive spinal cord lesions (3 or more spinal segments) are characteristic of NMO. Here we report a case of a 14 year old girl presented with weakness of all four limbs with left sided complete blindness. NMO was diagnosed because of characteristic MRI finding and positive Aquaporin 4 IgG positive.J MEDICINE July 2016; 17 (2) : 122-124